Charles Erskine Scott Wood - Unknown:::Creator::::::::::::
Charles Erskine Scott Wood stands in front of a trellis. C.E.S. Wood was an American author, civil liberties advocate, artist, soldier, attorney, and Georgist. He is best known as the author of the 1927 satirical bestseller, Heavenly Discourse. He lived with his second wife, Sara Bard Field, in Los Gatos, California, in a house named "The Cats" or the "Cats Estate." His friends included Ansel Adams, Albert M. Bender, Clarence Darrow, Eugene Debs,[11] Emma Goldman, Chief Joseph, Childe Hassam, Robinson Jeffers, Margaret Sanger, and John Steinbeck. Charlie Chaplin, Eleanor Roosevelt, and John Steinbeck.